Antiphosphlipid Syndrome Presented with Renovascular Hypertension - Savas Ozturk; Mukremin Uysal; Fulya Cosan; Banu Buyukaydin; Murat Inanc; Reyhan Diz-Kucukkaya; Isın Kılıcarslan; Aydin Turkmen; Rumeyza Kazancioglu (Archives of Clinical Nephrology - Peertechz Publications, 2016)
Renovascular pathologies are one of the treatable causes of hypertension. Antiphospholipid syndrome develops owing to a heterogeneous group of antiphospholipid antibodies which causes various thrombotic problems. This entity may effects very small vessels and sometimes leads to hypertension. We present a 55-year-old female with unilateral renal artery stent implantation because of renovascular hypertension. After application, a re-stenosis developed and in-stent angioplasty was performed, but it was required a nephrectomy because of haemorrhage. Severe ischemic nephropathy was detected in the nephrectomy material. She was diagnosed with antiphospholipid syndrome. Prolonged prothrombin time with hemorrhagic diathesis which coexisting thrombosis responded steroid therapy. But in follow-up, the thrombocytopenia developed, the patient could not recieve anticoagulant therapy and died due to a pulmonary embolism-like syndrome. This case reminds, renovascular hypertension is one of the major reasons of secondary hypertension and antiphospholipid syndrome always should be considered in thrombotic processes.